Effect of WFH Implementation on Employee Performance; with Work Motivation and Job Satisfaction as Mediation Variables and Information Technology Capability as Moderating Variables (Study on Administrative Employees of Universitas Brawijaya) - Virdani, Rachel Nitrogena; Noermijati, Noermijati; Hadiwidjojo, Djumilah (International Journal Labs, 2023)
The coronavirus disease (COVID-19) pandemic, which spread from March 2020 to April 2022, is very concerning. The government is making various efforts to reduce the spread of the virus, including implementing